Qualitative experiences of self-focus, distraction, and interactionist anxiety-performance mechanisms: What do players perceive? - Rich, S.; Zhang, S.; Jiang, K.; Wakefield, C.; Owen, R. (Journal of Sport & Exercise Psychology, 2025)
The negative effect of anxiety on performance has been explained via distraction (e.g., attentional control theory), self-focus (e.g., reinvestment theory), or an interaction of these mechanisms (e.g., interactionist hypothesis). For the first time, athletes` qualitative perception of all three mechanisms was explored. Ten amateur netball players completed an individual semistructured interview. Thematic analysis revealed three superordinate themes (distraction, self-focus, and interaction), two middle themes (sources and failure mechanisms), and a total of 10 subthemes (internal distractions, external distractions, impaired attentional control, overloaded attention, conscious motor processing, movement self-consciousness, deautomatization, distraction-induced self-focus, self-focus-induced distraction, and overload from simultaneous self-focus and distraction). Results suggest athletes notice instances of self-focus, distraction, and interactionist mechanisms. Interestingly, distraction and self-focus appeared to manifest a bidirectional relationship, whereby self-focus can be distracting and distraction can induce self-focus. This novel finding offers progress toward integrated rather than mutually exclusive conceptualizations of anxiety-performance mechanisms.